The Development of Creative Thinking Test Instruments with Torrance Indicators on Direct Current Electricity Materials - Tanjung, Y I; Nasution, I R (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
Direct current electricity matter is one of the many physics subjects containing concepts, principles and applied electricity where many problems can be solved with multiple solutions. Efforts to solve problems with multiple solutions and ideas can build students’ creative thinking. So this study aims to develop test instrument for creative thinking on Direct Current Electricity that meets the criteria for a good test instrument including validity, reliability, level of difficulty, discriminating power, and student responses. This type of research is Research and Development (RD) with a modified Borg Gall model consisted of research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing and operational product revision. Based on data analysis from the aspect of content validation of the test instrument by experts, seven valid items were obtained from the eight questions developed. Based on field testing, it was obtained that the reliability was in high category. In the aspect of difficulty level, the five questions are in easy category and two questions are in medium category. The distinguishing power of this test instrument is in the range of bad category, sufficient category, and good category. The results of the response test showed that respondents agreed that this test instrument was categorized as good to use. Overall, the results of the study indicate that the test instrument has met the requirements of a good test including validity, item analysis and response testing. Thus, the test instrument is feasible to train and measure students’ creative thinking.